6‐4: Organic Optical Sensor Based on a‐Si TFT Backplane Used in Fingerprint Identification under OLED Display. Issue 1 (28th June 2021) - Zhou, Lin; Qi, Chaoyang; Cheng, Jin; Wang, Ruichao; Kong, Dexi; BARBOT, Anthony; JOIMEL, Jérôme; Zhong, Kunjing; Li, Cheng; Che, Chuncheng
Abstract : The solution‐processed organic optical sensors based on a‐Si TFT backplane have been realized, which indicate the comparable performance compared to a‐Si photodiode optical sensors. Furthermore, the organic sensors demonstrate an extremely low absolute sensitivity threshold (also known as Noise Equivalent Power, NEP), which is down to 2.1 nW/cm 2 at 530nm.